An improved force-based impedance control method for the HDU of legged robots. (January 2019) - Ba, Kaixian; Yu, Bin; Gao, Zhengjie; Zhu, Qixin; Ma, Guoliang; Kong, Xiangdong
Abstract: Hydraulic drive mode enables legged robots to have excellent characteristics, such as greater power-to-weight ratios, higher load capacities, and faster response speeds than other robots. Nowadays, highly integrated valve-controlled cylinder, called hydraulic drive unit (HDU), is employed to drive the joints of these robots. However, various robot control issues exist. For example, during the walking process of legged robots, different obstacles are encountered, making it difficult to control such robots because the load characteristics of the ends of their feet change with the environment. Furthermore, although the adoption of HDU has resulted in high-performance robot control, the hydraulic systems of these robots still have problems, such as strong nonlinearity, and time-varying parameters. Consequently, robot control is very difficult and complex. This paper proposes an improved second-order dynamic compliance control system, impedance control, for HDU. The control system is designed to rectify the issues affecting the impedance control accuracy of the dynamic compliance serial–parallel composition between the HDU force control inner loop and the impedance control outer loop. Specifically, it consists of a compliance-enhanced controller and a feedforward compensation controller for the force control inner loop. Furthermore, the dynamic compliance composition of the inner and outer HDU control loops is rearranged. The results of experiments conducted indicate that the proposed method significantly improves the control accuracy compared to that of traditional force-based impedance control. Highlights: Key reasons affecting the accuracy of the traditional force-based impedance control. Dynamic compliance composition of both force inner loop and impedance outer loop. Control accuracy of the traditional force-based impedance control is improved.